3(2x+9)=5(x+6)

Simple and best practice solution for 3(2x+9)=5(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+9)=5(x+6) equation:



3(2x+9)=5(x+6)
We move all terms to the left:
3(2x+9)-(5(x+6))=0
We multiply parentheses
6x-(5(x+6))+27=0
We calculate terms in parentheses: -(5(x+6)), so:
5(x+6)
We multiply parentheses
5x+30
Back to the equation:
-(5x+30)
We get rid of parentheses
6x-5x-30+27=0
We add all the numbers together, and all the variables
x-3=0
We move all terms containing x to the left, all other terms to the right
x=3

See similar equations:

| 6x+(1/4)=(5/6) | | 11w=4 | | -3(y-1)-2y= | | 21x+6=2(7x+3) | | 8x(8x+6x)=7(16) | | 8x(8x+6x)=7(16 | | 310000-3x=x | | 4x-9=4x+2 | | 0=0.007x^2+0.003x-9 | | 7=9n-4n | | 1/48x=1/6 | | -9=15=v/3 | | 21/2y=75 | | 5(2y-1)=39 | | Y+1=2x-8 | | -7(u-3)=-3u+37 | | a+7=19+2a | | 9c-9=-11-5(c+6) | | -4y+48=-7(y-6) | | 11/3=8/x | | 83.5=3.5x-60 | | 180-(x+10)=2x+2x | | 18x=18x-11 | | (2x-14)+(-6+8×)=180 | | -2(c-11)+6=-8c-2 | | 5(2y-1)+y=39 | | 4x+30-2x+54=90 | | 5/8=n/11 | | 65=35^z | | 8(4u-1)-12u=11(2u-6 | | 5=7-h | | (x+4)/4=3/2 |

Equations solver categories